Efecto del extracto crudo del fruto de morinda citrifolia l. (noni) y vitis vinífera l. (uva) sobre los niveles séricos de malondialdehído en rattus rattus var. norvegicus hiperglicémicas” - Blas Torres, Kamy Jhancy (2017)
In the present research the effect of the crude extract of the fruit of Morinda citrifolia L. (noni) and Vitis vinífera L. (uva) on the serum levels of malondialdehyde in Rattus rattus var. norvegicus hyperglycemic. 21 male albino rats, 2 to 3 months old, whose weights ranged from 250 to 300g and were randomly distributed in 3 experimental groups; Control, problem 1 and problem 2. The control group was administered orally 2 mL of 0.9% NaCl, groups of problem 1 and 2 were given crude extract of Morinda citrifolia L. and Vitis vinífera L. at a dose of 155 mg/kg b.w. and 310 mg/kg b.w. Respectively, for a period of 21 days; hyperglycemia was induced with streptozotocin (45 mg/kg i.p.), at 48 hours the blood glucose levels were randomly measured. The cardiac puncture samples were then taken, which were used to determine the serum levels of malondialdehyde, according to the colorimetric method of thiobarbituric acid reactive substances (TBARS). The crude extract of Morinda citrifolia L. and Vitis vinífera L. at a dose of 310 mg/kg b.w was shown to significantly reduce the serum levels of malondialdehyde in Rattus rattus var. norvegicus hyperglycemic (p = 0.044) and according to the Pearson correlation coefficient (P=0.474), there is a directly proportional relationship between blood glucose levels and serum levels of malondialdehyde